Pendidikan Moderasi Beragama Dalam Keluaga Berbasis Al-Qur’an - Oki Setiana Dewi; Akmal Rizki Gunawan Hsb (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Religious Moderation Education in Families Based on Al-Qur'anThe purpose of this study is to analyze the theoretical concept of religious moderation education in families based on al-Qur'an. Given that the family context in the policy of strengthening religious moderation by the Ministry of Religious Affairs of Indonesia has not been a priority compared to the social and educational context. In this study, the author uses the method of tafsir maudhu'i, which serves to explore the thematic idea of "religious moderation education in the family" comprehensively in the Qur'an. This paper found that there are four concepts of religious moderation education in the Quran-based family, namely; First, family education with creed vision. Second, family education with a humanitarian vision. Third, family education with a national vision. Fourth, family education with a vision of justice. In addition, it can also be seen that there are eight terms of religious moderation in the Qur'an, namely; First, al-Wasth (Ø§Ù„ÙˆØ³Ø·) which means just, best people, and not excessive. Secondly, al-Sadad (Ø§Ù„Ø³Ø¯Ø§Ø¯) is right on target and means right. Third, al-Qasd (Ø§Ù„Ù‚ØµØ¯) means having good and right goals, determination, and direction. Fourth, al-Istiqamah (Ø§Ù„Ø¥Ø³ØªÙ‚Ø§Ù…Ø©) is consistent. Fifth, al-Khairiyah (Ø§Ù„Ø®ÙŠØ±ÙŠØ©) is the best people. Sixth, al-Adl (Ø§Ù„Ø¹Ø¯Ù„) is the people who always uphold justice. Seventh, al-Yusr (Ø§Ù„ÙŠØ³Ø±) is the people who always provide ease and eliminate difficulties. Eighth, al-Hikmah (Ø§Ù„ØÙƒÙ…Ø©) is a people who always pay attention to all sides of things or problems.